PENGARUH FAKTOR ORGANISASIONAL DAN KARAKTERISTIK INDIVIDU TERHADAP AKUNTABILITAS KINERJA MELALUI SISTEM PENGUKURAN KINERJA - Agus Shafrizal; Taufeni Taufik; Azwir Nasir (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The purpose of this study was to examine the relationship of organizational factors and individual characteristics against performance accountability through performance measurement system in the Government of Kampar. This research was conducted against the 52 organizations device area in Kampar. Respondents employed in this research totalled 116. The independent variable in this study was organizational factors: organizational commitment, organizational culture, training, individual characteristics factors: self efficacy, conscientiousness. The dependent variable is the performance accountability. Intervening variable is a system of performance measurement. Data collected from 116 respondents further analyzed with the help of software WarpPLS version 5.0. Results of the study prove that factors that affect performance accountability is a organizational commitment and training. Factors that affect the performance measurement system is the organizational commitment, organizational culture, self efficacy and conscientiousness. Through a system of performance measurement as an intervening variable obtained results certify organizational commitment, organizational culture, self efficacy and positive effect toward conscientiousness performance accountability.